SOSIALISASI PEMANFAATAN PEKARANGAN DI WILAYAH PESISIR UNTUK MENINGKATKAN KETAHANAN PANGAN DAN GIZI MASYARAKAT DESA TANJUNG BUNGA, KECAMATAN WAWOLESEA, KABUPATEN KONAWE UTARA - La Ode Adi Parman Rudia; Haeruddin; Rahman Hasima; Idris Saputra; Sri Wahyuni Basoka; fitriah amir (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Tanjung Bunga Village, located in Wawolesea District, North Konawe Regency, is one of the coastal villages endowed with abundant natural resources, both terrestrial and marine. Most of its residents work as fishermen and live in houses facing the sea. However, the use of home yards has not yet been optimized as a source of food or for improving family nutrition. Based on the identification results, two main problems were found: the low awareness of the community regarding the importance of yard utilization and the lack of knowledge about proper management techniques. To address these issues, a community service activity was carried out through a socialization program on yard utilization in coastal areas. This activity aimed to enhance the awareness and knowledge of fishing communities about the importance of productive yard management. The results showed an increase in understanding and motivation among participants to utilize their home yards as alternative food sources and as an effort to improve family nutrition. It can be concluded that the socialization program has successfully increased participants’ awareness of the importance of yard utilization to strengthen food security and community nutrition. Keywords: Coastal area, yard utilization, food security